Daily socket comfort in transtibial amputee with a vacuum-assisted suspension system: study protocol of a randomized, multicenter, double-blind multiple N-of-1 trial - Rémi Klotz; Guilhem Emile; Jean-Christophe Daviet; Mathieu De Sèze; Julien Godet; Renaud Urbinelli; Agata Krasny-Pacini (BMC, 2023)
Abstract Background The main aim of this paper is to present the feasibility of rigorously designed multiple N-of-1 design in prosthetics research. While research of adequate power and high quality is often lacking in rehabilitation, N-of-1 trials can offer a feasible alternative to randomized controlled group trials, both increasing design power at group level and allowing a rigorous, statistically confirmed evaluation of effectiveness at a single patient level. The paper presents a multiple N-of-1 trial protocol, which aim is to evaluate the effectiveness of Unity, a prosthetic add-on suspension system for amputees, on patient-reported comfort during daily activities (main outcome measure), prosthesis wearing time, perception of limb-prosthesis fitting and stump volume and functional walking parameters. Methods Multicenter, randomized, prospective, double-blind multiple N-of-1 trial using an introduction/withdrawal design alternating Unity connected/disconnected phases of randomized length on twenty patients with unilateral transtibial amputation. The primary outcome measure is the Prosthetic Socket Comfort Score (SCS), a validated measure of comfort, administered daily by an phone app designed for the study. Secondary outcomes measures will be collected during the 50 days period of the N-of-1 trial: (1) by the same app, daily for patient-reported limb-prosthesis fitting, stump volume variation, and daily wearing time of the prosthesis; (2) by a pedometer for the number of steps per day; (3) by blind assessors in the rehabilitation center during adjustment visits for functional walking parameter (L-Test, 6-minute walk test), and by the patient for the QUEST, and ABC-S. Effectiveness of the Unity system regarding SCS and daily secondary outcome measures will be tested by randomization test. The secondary outcome measures assessed during visits in the rehabilitation center will be analyzed by Non Overlap of All pairs. An estimate of the effect on the amputee population will be generated by aggregating each individual clinical trial (N-of-1 trial) by Hierarchical Bayesian methods. Discussion This study protocol was designed to answer the question "which device is best for THIS patient" and to conclude at a group level on the effectiveness of a new devic, using a Multiple N-of-1 trial, which is promising but underused in prosthetics research so far. Trial registration N° ID-RCB 2020-A01309-30 Clintrial.gov : NCT04804150 - Retrospectively registered March 20th 2021.